Antropometric Evaluation Of Gentur's Cheiloplasty Method In Unilateral Cleft Lip - Septrina, Rani; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2016)
Background: Cheiloplasty, the earliest surgical procedure in cleft lip and palate patient, has impact on functional and aesthetical appearance1. The Gentur’s technique is a method of cleft lip surgery that has been developed by him and has been used in RSUPN Cipto Mangunkusumo/Faculty of Medicine Universitas Indonesia2. It uses the rotation-advancement, small triangular, preventing notching concepts with some other details to overcome the wide cleft. This study was conducted to answer whether the Gentur’s technique gives symmetrical result in anthropometric measurements. Methods: Cross sectional analytic study will be taken from medical record in 14 unilateral cleft lip patients underwent cheiloplasty procedure. Direct anthropometric data before and after procedure were analyzed using SPSS17. Anthropometric data such as cupid’s bow, vertical height, horizontal height, vermillion and nostril were noted. Results: From 14 patients, we found 9 patients who underwent surgery in 3 months of age (64.3%) are mostly female (n=9, 64.3%), have complete defect (n=12, 85.8%) and left sided defect (n=8, 57.1%). Gentur’s technique is able to produce significant lip and nose symmetry (CI 95%, pvalue <0.005) in cupid’s bow, vertical height, horizontal height, thickness of vermillion and nose. By doing this technique, the author is able to create good lip and nose symmetry (78.57%) even in wide defect (64.3%) and palatal collapse (57.1%). Conclusion: Gentur’s technique is able to utilize tissue deficiency to create ideal lip and nose in unilateral cleft lip repair even in patients with wide gap.